The effect of changes in iron-endpoint during Peirce–Smith convertingon PGE-containing nickel converter matte mineralization - Thyse, E.; Akdogan, G.; Eksteen, Jacques (Elsevier, 2011)
PGE-containing nickel-copper converter matte is blown to an iron-endpoint during Peirce–Smith conversion. The matte is granulated after conversion and the process can be described as fast cooling. The effect of changes in the iron-endpoint on matte mineralization during granulation or fast cooling is poorly understood. The aim of the study was to investigate the mineralogy and basic mineral chemistry of PGE-containing nickel converter matte as a function of iron-endpoints 5.17 wt%, 0.99 wt% and 0.15 wt%. A combination of mineralogical analytical techniques was applied to methodically characterise the converter matte. Representative sub-samples for the respective iron-endpoints were characterised using quantitative X-ray diffractometry (QXRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), high-resolution scanning transmission electron microscopy (HRSTEM) and bulk chemical and instrumentation methods. Moreover, solidification paths were created for the respective iron-endpoints to use as an assistant tool in understanding matte mineralogy.The matte mineralogy for iron-endpoint 5.17 wt% is characteristic of a significantly higher heazlewoodite relative abundance (77.89%) in comparison with that for iron-endpoints 0.99 wt% (62.92%) and 0.15 wt% (63.67%). Iron-endpoints 0.99 wt% and 0.15 wt% are in contrast, characteristic of a higher chalcocite relative abundance (18.56% and 17.86% respectively) in comparison with 12.04% for the high iron-endpoint. The lower iron-endpoints are further characteristic of a significantly higher alloy relative abundance in comparison with the high iron-endpoint. The PGE-containing nickel-dominant alloy phase for the high iron-endpoint is extremely fine grained, set in the heazlewoodite matrix and characteristic of the exsolution origin. The NiCu-dominant, PGE-containing alloy phases for iron-endpoints 0.99 wt% and 0.15 wt% are characterised by an exsolution origin followed by exsolution modifications probably due to PGE saturation at an early cumulus stage and the presence of other elements.